2022
DOI: 10.5187/jast.2021.e132
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced γ-aminobutyric acid and sialic acid in fermented deer antler velvet and immune promoting effects

Abstract: Deer antler velvet is widely used in traditional medicine for its anti-aging, antioxidant, and immunity-enhancing effects. However, few studies have reported on the discovery of probiotic strains for deer antler fermentation to increase functional ingredient absorption. This study evaluated the ability of probiotic lactic acid bacteria to enhance the concentrations of bioactive molecules (e.g., sialic acid and gamma-aminobutyric acid [GABA]) in extracts of deer antler velvet. Seventeen strains of L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 45 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Compared to other animal models, C. elegans has a relatively limited lifespan, with a reproductive cycle that lasts only a few days. Therefore, C. elegans has been usefully utilized as an efficient animal replacement model that can rapidly demonstrate health improvement effects [ 21 , 22 ]. Supplements of methionine significantly increased the lifespan of C. elegans , regardless of the source or percentage of methionine; feed grade L-Met 95%, which is composed of a single type of methionine, the L-type, with 5% of Corynebacterium fermentation medium from the production process, demonstrated the best performance of C. elegans lifespan [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to other animal models, C. elegans has a relatively limited lifespan, with a reproductive cycle that lasts only a few days. Therefore, C. elegans has been usefully utilized as an efficient animal replacement model that can rapidly demonstrate health improvement effects [ 21 , 22 ]. Supplements of methionine significantly increased the lifespan of C. elegans , regardless of the source or percentage of methionine; feed grade L-Met 95%, which is composed of a single type of methionine, the L-type, with 5% of Corynebacterium fermentation medium from the production process, demonstrated the best performance of C. elegans lifespan [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…400%) and 30% lower levels of oxalic acid, an anti-nutritive factor ( Filannino et al, 2017 ). Yoo et al (2022) also reported that fermentation of deer antler velvet with Lacticaseibacillus rhamnosus LFR20-004 and Latilactobacillus sakei LFR20-007 augmented the concentration of bioactive amino acids, such as sialic acid and GABA. Fermented antlers exerted potent immune-enhancing activity by stimulating in the production of IL-6, IL-10, IFN-γ and TNF-α, possibly due to an increase in these bioactive molecules ( Yoo et al, 2022 ).…”
Section: Immunoregulatory Effect Of Lactic Acid Bacteria Fermented He...mentioning
confidence: 91%
“…For the lifespan analysis, egg-bearing worms were bleached using a sodium hypochlorite‒sodium hydroxide solution (Sigma‒Aldrich), and the newborn worms were synchronized to L1 stage worms on NGM plates at 25°C ( 57 ). After 3 days, young adult L4 stage worms were plated on 35-mm-diameter NGM plates seeded with OP50, IDCC 2102, IDCC 4301, and LGG.…”
Section: Methodsmentioning
confidence: 99%